Pertanggungjawaban Pelaku Usaha Jual Beli Mobil Bekas Terkait Keamanan Mobil Yang Tidak Sesuai Standart Karena Tidak Melakukan Uji Emisi - Isna Nurrosyidah; HR. Adianto Mardijono (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Non-compliance by used car buying and selling businesses with emission test obligations not only harms consumers in terms of health and comfort, but also adversely affects the environment. So it becomes the responsibility of the business actor if something bad happens to the consumer due to the business actor not ensuring the safety of the used car because they did not carry out an emissions test. The purpose of this study is to determine the responsibilities of used car buying and selling businesses regarding the safety of used cars and the obligation to test emissions on used car vehicles. The methodology used in this study was a normative study using both a statutory and conceptual approach.. With the result that business actors have an obligation to fulfill the quality including the safety of used cars in accordance with Article 8 of Law Number 8 of 1999 concerning Consumer Protection. In this way, ensuring that every aspect of safety, including emissions, complies with used car safety standards, becomes a form of business actor's responsibility to consumers. It is the obligation of used car business actors to ensure that every used car is in a suitable condition for use according to the standards regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation, in order to improve the quality of safety standards, the specified environment, and not harm used car users in this is consumer.